2015
DOI: 10.1002/jcp.25185
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐Catulin Co‐Localizes With Vimentin Intermediate Filaments and Functions in Pulmonary Vascular Endothelial Cell Migration via ROCK

Abstract: The ubiquitous α-catulin acts as a scaffold for distinct signalosomes including RhoA/ROCK; however, its function is not well understood. While α-catulin has homology to the cytoskeletal linkers α-catenin and vinculin, it appears to be functionally divergent. Here we further investigated α-catulin function in pulmonary vascular endothelial cells (VEC) on the premise that α-catulin has a unique cytoskeletal role. Examination of endogenous α-catulin intracellular localization by immunofluorescence revealed a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…In recent years, regulatory factors of vimentin have been identified. For example, alpha-catulin colocalizes with vimentin intermediate filaments and functions in pulmonary vascular endothelial cell migration via ROCK [ 39 ], and proteomic analysis revealed the important role of vimentin in human HeLa cells [ 40 ]. Here, we found that vimentin was upregulated in human GC tissues and cell lines, and the upregulation of vimentin promoted the aggressiveness of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, regulatory factors of vimentin have been identified. For example, alpha-catulin colocalizes with vimentin intermediate filaments and functions in pulmonary vascular endothelial cell migration via ROCK [ 39 ], and proteomic analysis revealed the important role of vimentin in human HeLa cells [ 40 ]. Here, we found that vimentin was upregulated in human GC tissues and cell lines, and the upregulation of vimentin promoted the aggressiveness of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that intermediate filament architecture is reorganized in response to cell migration stimuli. α-Catulin, a scaffold for the ROCK signalosome (Park et al, 2002 ), co-localizes with vimentin intermediate filaments and contributes to vascular endothelial cell migration (Bear et al, 2016 ). In addition, vimentin filaments are also essential for VASP localization and phosphorylation by cGMP dependent kinase in endothelial cells (Lund et al, 2010 ).…”
Section: Intermediate Filaments and Modulation Of Signal Transductionmentioning
confidence: 99%
“…However, α-catulin is expressed by heterogeneous populations of HSPCs, including stromal cells and ECs (Chen et al 2016). Expression of α-catulin indicates EC activation and migratory state (Bear et al 2016). Similarly, such expression may also allow for the identification of metabolically activated HSPCs in BM perisinusoidal niches.…”
Section: Architecture Of Bone Marrow Vasculature and Spatial Localizamentioning
confidence: 99%